2015
DOI: 10.4103/0974-8490.147227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analgesic, antipyretic and anti-inflammatory activity on Cordia dichotoma G. Forst. Leaf

Abstract: Background:Cordia dichotoma G. Forst. is an important medicinal plant of family Boraginaceae. Traditionally, its leaves are used to treat fever, headache, and joint pain but its medicinal activities have not been proven by research.Objective:To evaluate the analgesic, anti-inflammatory, and antipyretic activity of C. dichotoma G. Forst. leaf extract.Material and Methods:The various extracts of leaf powder were prepared by using soxhlet apparatus. The methanol extract was selected for pharmacological study. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Paw edema induced by carrageenan is an acute model of inflammation widely used to evaluated anti-inflammatory effect of natural products. [ 31 32 33 ] After injection, carrageenan immediately produces edema, hyperalgesia, and erythema, resulting from the action of proinflammatory agents such as bradykinin, histamine, tachykinins, and complement. [ 34 ] Our results showed that all extracts present anti-inflammatory effects, being GOJI extract more effective in reducing paw edema than BLUE and CRAN extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Paw edema induced by carrageenan is an acute model of inflammation widely used to evaluated anti-inflammatory effect of natural products. [ 31 32 33 ] After injection, carrageenan immediately produces edema, hyperalgesia, and erythema, resulting from the action of proinflammatory agents such as bradykinin, histamine, tachykinins, and complement. [ 34 ] Our results showed that all extracts present anti-inflammatory effects, being GOJI extract more effective in reducing paw edema than BLUE and CRAN extracts.…”
Section: Discussionmentioning
confidence: 99%
“…dichotoma G. Forst. methanolic leaf extracts are analgesic, antipyretic and anti-inflammatory (Gupta and Kuar, 2015). Ferreira Matias et al (2015) reported the presence of luteolin (3′,4′,5,7-tetrahydroxyflavone), apigenin and lupeol in C. dichotoma G. Forst.…”
Section: Medicinal Propertiesmentioning
confidence: 99%
“…Methanol extract high dose (400 mg/kg) was found to be highly significant as compared to standard drug 36 . Therefore, results from various published work confirm and supports the traditional use of C. dichotoma for management of pyrexia, inflammation and painful conditions.…”
Section: Analgesic Anti-inflammatory and Antipyretic Activitymentioning
confidence: 99%